SARS-CoV-2 infection does not affect ovarian reserve in women undergoing assisted reproduction - Campitiello, Mara; Cruz, María; González-Ravina, Cristina; Vergara, Vanessa; Pacheco, Alberto; Remohí, José; Miranda, Antonio Requena (Clinical Journal of Obstetrics and Gynecology, 2023)
Information regarding the effects of the novel coronavirus on human reproduction is currently limited. The objective of our work was to assess whether, in women who have passed the disease, there was a variation in the ovarian reserve through the determination of AMH levels. During May-June 2020, women performing an Assisted Reproductive treatment and who had a positive IgG for SARS-CoV-2 were included in the study; this group of women had a previous AMH determination of no more than 6 months. Women were stratified into two groups, according to their previous AMH levels: low responders (AMH< 1 ng/ml) or normal-high responders (AMH ≥ 1 ng/ml) Statistical analyses were performed using the Statistical Package for Social Sciences 19.0 (IBM Corporation, Armonk, NY, USA). A total of 46 patients were included in the study; 16 women were diagnosed as having low ovarian reserve (AMH < 1 ng/ml), with an average age of 38.6 years, whereas 30 were classified as having normal ovarian reserve (AMH ≥ 1 ng/ml), with an average age of 34.7 years. Generally, the data show no variation in AMH levels before and after SARS-CoV-2 infection (1.73 ng/ml vs. 1.61 ng/ml, respectively). However, when we analyzed these differences according to the study groups, the results were consistent with the patient's ovarian status. It is possible to conclude that the fact of having passed the disease does not affect the ovarian reserve status but the degree of the variation of AMH levels depending on the patient was a low or high responder.